2019
DOI: 10.1088/1475-7516/2019/10/008
|View full text |Cite
|
Sign up to set email alerts
|

Viable inflationary magnetogenesis with helical coupling

Abstract: We consider helical coupling to electromagnetism and present a simple scenario of evolution of the coupling function leading to a viable inflationary magnetogenesis without the problem of back-reaction. In this scenario, helical magnetic fields of strength of order up to 10 −7 G, when extrapolated to the current epoch, can be generated in a narrow spectral band centered at any reasonable wavenumber by adjusting the model parameters. We discuss implications of this model for baryogenesis, which impose additiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“…Basing on this observation, we considered in [21] a linear dependence of as a function of conformal time: ′ ( ) = const, 1 ≤ ≤ 2 , joining the time epochs with constant values of . The growth of ℎ in this case is exponential for one of the helicities in the interval 1 < < 2 .…”
Section: Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…Basing on this observation, we considered in [21] a linear dependence of as a function of conformal time: ′ ( ) = const, 1 ≤ ≤ 2 , joining the time epochs with constant values of . The growth of ℎ in this case is exponential for one of the helicities in the interval 1 < < 2 .…”
Section: Scenariomentioning
confidence: 99%
“…Back-reaction on inflation and on the dynamics of the inflaton field in the scenario under consideration was estimated in [21] with the upper bound…”
Section: Back-reaction On Inflation and Baryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Many models of evolution of I and f were tried in the literature to overcome these difficulties and to obtain the highest possible value of primordial magnetic field. Given the diversity of these approaches, and based on our preliminary studies [49,50], we suggested in [51] to seek for modelindependent constraints imposed by all these limitations for the whole class of models described by (1). This is similar in spirit to the previous studies [10,62], which, however, imposed a priori ansatzes for the evolution of the couplings and did not take into account the Schwinger effect.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar in spirit to the previous studies [10,62], which, however, imposed a priori ansatzes for the evolution of the couplings and did not take into account the Schwinger effect. Here, we will review the results of our investigation in [49][50][51].…”
Section: Introductionmentioning
confidence: 99%